ISLAM, EMPIRE, AND IDEOLOGY: Lord Stanley and the Intersection of Islam and Politics in 19th Century Europe - Hasbi, Baiquni; Khitam, Husnul (UIN Sumatera Utara, 2024)
Abstract: This article delves into the political biography and thought of Lord Henry Stanley, a member of British House of Lords, who embraced Islam in the mid-19th century. Through a global history perspective, this article’s analysis draws on Stanley’s personal writing, historical records, and parliamentary debates to trace his trajectory and analyze his political thought. By locating Stanley amidst the context of 19th-century international politics, Stanley’s biography and political thought challenged the dominant narrative portraying European officers merely as colonialist and imperialist. It also complicates the conventional narrative between Islam and the Christian West dominantly depicted as always an antithesis. Throughout his career in the British House of Lords, Henry Stanley consistently pinpointed the values of justice, which he believed were deeply rooted in the Islamic political system, amidst the increasing racialization of Muslims both in Britain and within the increasingly Eurocentric international community. Although Stanley did not challenge British imperialism in Asia and Africa, he did challenge several British policies in India and the Straits of Malacca, which he thought was the result of British arrogant attitude toward non-European political order. Keywords: Lord Stanley, European empire, Islam, modern, international politics